1992
DOI: 10.1128/jcm.30.5.1179-1182.1992
|View full text |Cite
|
Sign up to set email alerts
|

Stability of human immunodeficiency virus type 1 antibodies in whole blood dried on filter paper and stored under various tropical conditions in Kinshasa, Zaire

Abstract: The use of whole-blood spots on filter paper for the detection of antibody to human immunodeficiency virus type 1 (HIV-1) was evaluated during a 20-week period under a variety of storage environments simulating the harsh tropical field conditions in Kinshasa, Zaire. During the first 6 weeks of storage, all replicates of highand low-titer HIV-1-positive reference samples remained positive by enzyme immunoassay and Western blotting (immunoblotting), and all replicates of HIV-1-negative samples remained negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(41 citation statements)
references
References 8 publications
1
39
0
1
Order By: Relevance
“…The ®lter paper samples were frozen for a median of greater than 14 1/2 months prior to rubella testing, which could have affected the results. However, a study in Zaire demonstrated stability of HIV IgG antibody titers in a variety of environmental conditions over a 20-week period [Behets et al, 1992]. The use of an adjustment factor brought the results back into the appropriate range described for serum results in the package insert.…”
Section: Discussionmentioning
confidence: 99%
“…The ®lter paper samples were frozen for a median of greater than 14 1/2 months prior to rubella testing, which could have affected the results. However, a study in Zaire demonstrated stability of HIV IgG antibody titers in a variety of environmental conditions over a 20-week period [Behets et al, 1992]. The use of an adjustment factor brought the results back into the appropriate range described for serum results in the package insert.…”
Section: Discussionmentioning
confidence: 99%
“…It is very important to dry biological samples completely before storage or transportation. Typically, the drying time of biomaterial depends on sample volume and type of membrane carrier [26]. Due care must be taken to ensure that samples are not heated, stacked or allowed to come into contact with other samples or surfaces.…”
Section: Types Of Membrane Carriers Biomaterials Collection Processimentioning
confidence: 99%
“…Limited stability of HIV-1 RNA in liquid plasma and the need for expedient collection, processing and transport of samples on dry ice or liquid nitrogen; although the logistics of specimen handling are being addressed in developing countries, few studies have examined the technical challenges and immediate sample processing and refrigeration are often unavailable. As the developing world bears a disproportion of the global population of people with AIDS and that clinical trials are planned for many of the developing countries, there exists a need to develop a simple and improved sampling methods which can be widely applied under difficult field conditions [10] - [13], [21], [38].…”
Section: Introductionmentioning
confidence: 99%
“…Dried plasma can be stored for prolonged periods of time at ambient temperature without adversely affecting quantitative HIV-1 RNA determination or changing the categorical result (from positive to negative). Also stable in dried plasma are a growing list of HIV-1 analytes: antibodies, antigens, RNA, and proviral DNA that are unexpectedly stable when dried onto a solid matrix [10], [14], [15], [18] - [20]. Athicha et al, 2017 alongside Sally et al, 2015 reported that the ultimate utility of DPS at the global level will depend on the ability of the amplification primers to recognized and amplify different clades with equal efficiency because in their study, the Limit of Detection (LOD) test from the improved DNA extraction method DBS, HIV-1 DNA was ≥ 250 copies/ml [21], [38].…”
Section: Introductionmentioning
confidence: 99%